2014
DOI: 10.1002/ajh.23821
|View full text |Cite
|
Sign up to set email alerts
|

Core‐binding factor acute myeloid leukemia: Heterogeneity, monitoring, and therapy

Abstract: Core binding factor acute myelogenous leukemia (CBF AML) constitutes 15% of adult AML and carries an overall good prognosis. CBF AML encodes two recurrent cytogentic abnormalities referred to as t(8;21) and inv (16). The two CBF AML entities are usually grouped together but there is a considerable clinical, pathologic and molecular heterogeneity within this group of diseases. Recent and ongoing studies are addressing the molecular heterogeneity, minimal residual disease and targeted therapies to improve the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 154 publications
9
82
2
2
Order By: Relevance
“…Patients with t-AML are more prone to a poor prognosis and cytogenetic findings. Core binding factor abnormalities are associated with an improved outcome in patients with AML (39)(40)(41). However, in the present cohort, t (15,17) appeared to have a good effect on the outcome of disease, even in patients with t-AML (42)(43)(44)(45).…”
Section: Characteristiccontrasting
confidence: 51%
“…Patients with t-AML are more prone to a poor prognosis and cytogenetic findings. Core binding factor abnormalities are associated with an improved outcome in patients with AML (39)(40)(41). However, in the present cohort, t (15,17) appeared to have a good effect on the outcome of disease, even in patients with t-AML (42)(43)(44)(45).…”
Section: Characteristiccontrasting
confidence: 51%
“…CBF AMLs generally represent an AML subgroup with a favorable outcome. 24 Comparing the expression levels of both mature miRNAs strands confirmed miR-139-5p to be the guide and miR-139-3p to be the passenger strand (Supplementary Figure 1b). The expression data suggested that miR-139-5p is upregulated in terminally differentiated myelomonocytic cells to control proliferation, whereas it is suppressed in normal and malignant stem and progenitor cells.…”
Section: Resultsmentioning
confidence: 68%
“…Another study with 481 AML patients indicated that 20% of the CBF-AML cytogenetic group had FLT3 mutations 27 . On the other hand, KIT mutations have been observed for 6.6–46.1% of CBF-AML patients 28 . NPM1 plays an important role in ribosomal protein assembly, transport, prevents aggregation of nuclear proteins and regulates transcriptional activity of p53 26 .…”
Section: Cooperating Mutations In Cbf Leukemiamentioning
confidence: 99%
“…Although the CBF genetic rearrangements in AML patients are reported to be associated with relatively favorable prognosis 32,33 , only 40–60% of adult CBF-AML patients exhibit long-term survival 28 . Additionally all treatment regimens are associated with significant relapse related morbidity and mortality 34,35 .…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation